(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The rapid advancement of digital technologies has transformed how micro, small, and medium enterprises (MSMEs) engage with customers and maintain competitiveness in increasingly dynamic markets. Despite this trend, many MSMEs in Indonesia continue to face challenges in adopting effective digital marketing strategies that enhance visibility and customer interaction. This study aims to examine the effectiveness of Google My Business (GMB) as a digital marketing tool for improving visibility and customer engagement in the catering MSME Dapur Bu Dedek, located in Deli Serdang Regency, Indonesia. Employing a qualitative case study approach, the research utilized secondary data derived from six months of GMB performance reports to analyze patterns of customer engagement and platform-driven interactions. The findings reveal that GMB significantly contributes to strengthening the enterprise’s digital presence by generating substantial profile views, navigation requests, and direct interactions, with mobile-based access accounting for the majority of engagement. These results suggest that GMB not only facilitates visibility but also fosters meaningful customer connections that are critical for sustaining business growth. The study contributes to the growing body of literature on digital marketing adoption in MSMEs by emphasizing the strategic role of GMB in shaping consumer engagement behaviors. In practical terms, the research provides actionable insights for MSME owners and policymakers on optimizing digital platforms to enhance competitiveness and resilience in the digital economy.